2010
DOI: 10.1063/1.3327236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultraviolet radiation on slow-relaxation processes in ferroelectric capacitance structures

Abstract: Articles you may be interested inModification of energy band alignment and electric properties of Pt/Ba0.6Sr0.4TiO3/Pt thin-film ferroelectric varactors by Ag impurities at interfaces Suppression of slow capacitance relaxation phenomenon in Pt/Ba0.3Sr0.7TiO3/Pt thin film ferroelectric structures by annealing in oxygen atmosphere Appl. Phys. Lett.The effects of ultraviolet ͑UV͒ irradiation on the relaxation processes in Ba 0.3 Sr 0.7 TiO 3 thin film capacitors were experimentally investigated in a range of wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Their concentration reduces with the increase of the O 2 deposition pressure and improvement of the SRO film crystal structure. This is further confirmed by the measured extremely low carrier mobility in films grown at O 2 deposition pressure below 50 mTorr, as the non-equilibrium charge carriers are usually trapped by the defects24. The carrier concentrations measured for the films grown at O 2 deposition pressure above 50 mTorr are in agreement with the previously observed values2526.…”
Section: Discussionsupporting
confidence: 89%
“…Their concentration reduces with the increase of the O 2 deposition pressure and improvement of the SRO film crystal structure. This is further confirmed by the measured extremely low carrier mobility in films grown at O 2 deposition pressure below 50 mTorr, as the non-equilibrium charge carriers are usually trapped by the defects24. The carrier concentrations measured for the films grown at O 2 deposition pressure above 50 mTorr are in agreement with the previously observed values2526.…”
Section: Discussionsupporting
confidence: 89%
“…Measurements of the UV absorption coefficient, carried out with BSTO film-based planar structures, have revealed a band-edge tailing (%0.1 eV) that can be attributed to the high density of shallow traps. 7 Apart from the shallow traps, there are deep trap centers that can be formed, in particular, by interstitial oxygen atoms incorporated during the deposition of a BSTO film in an oxygen atmosphere at T ¼ 675 C and by complexes formed by O-vacancies and metal ions. 28,29 For BSTO films, trap centers with different energy spacings (E t ) from the conduction band bottom have been reported: 0.2 eV and 1.31 eV, 30 0.3 eV, 0.55 eV, and 0.88 eV, 29 0.335 eV, 31 0.51 eV, 13 and 0.83 eV.…”
Section: Remnant Capacitance Relaxationmentioning
confidence: 99%
“…However, BSTO films show a slow dielectric relaxation, which is the critical problem in the case of the pulse-controlled operation mode, when the capacitance does not return to its initial value after the end of a control voltage pulse, but slowly relaxes in the course of time. [4][5][6][7] This results both in the ambiguity in the controlled phase, frequency, or delay and in their variation with the control-pulse parameters (amplitude, duration, repetition frequency). 7,8 An understanding of the physical mechanisms of the slow dielectric relaxation in perovskite-oxide films and a search for the possibility of speeding-up the relaxation are important for the development of not only fast microwave devices, but also high-capacity ferroelectric memories, because the same mechanisms may be responsible for the polarization fatigue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, intensive experimental research has been performed to investigate the radiation effect of ferroelectric thin films. [5][6][7][8][9][10][11][12][13][14][15][16][17] For example, Menou et al 8 had demonstrated that the electrical characteristics of Pt/SrBi 2 Ta 2 O 9 (SBT)/Pt ferroelectric capacitor changed significantly during or after irradiation. In their work, both "fatigue-like" (polarization reduction) and/or "imprint-like" (voltage shift) phenomena were observed.…”
mentioning
confidence: 99%